Porth's Pathophysiology : Concepts of Altered Health States - Norris, Tommie L. (Philadelphia : Wolters Kluwer, 2025)
"Make the most of your pathophysiology course and master the knowledge to ensure clinical success. Trusted for more than 30 years and updated to reflect today's nursing challenges, this engaging text makes complex concepts accessible and helps you easily and confidently grasp normal body function, the effects of disease on body systems, and the body's ability to compensate and adapt. This edition also considers the many technological advances that allow healthcare providers to diagnose earlier and with more accuracy"--
Includes bibliographical references and index.
Keywords: Disease; Pathologic Processes; Physiological Phenomena; MEDICAL / Pathophysiology; Nurses Instruction